Do multisectoral New Keynesian models match sectoral data? - Philippe Andrade; Viacheslav Sheremirov (Federal Reserve Bank of Boston, 2022)
We document empirical regularities of disaggregated inflation and consumption and study whether multisectoral New Keynesian models can explain them. We focus on higher moments of the inflation and consumption growth distributions as well as on the contemporaneous comovement of these two variables. We find that the sectoral distributions of inflation and consumption growth are asymmetric, with inflation skewed negatively and consumption growth positively. Both distributions are highly leptokurtic. In the full sample, from the mid-1980s through 2021, sectoral inflation and consumption growth overall correlate negatively, indicating the prevalence of supply shocks over demand shocks. The negative correlation is robust across historical episodes during this period, except during the COVID-19 pandemic, when inflation and consumption growth comoved positively. While the baseline model can match some of these facts for a specific shock process, in its baseline setup the model struggles to match them simultaneously.
Keywords: E12; E31; E32; E52; 330; disaggregated inflation; multisectoral models; idiosyncratic shocks